Eradicating Child Marriage in Sukabumi Through The Role of Plan International - Ledya Putri Wilona; Elfitra Elfitra (Interdisciplinary Social Studies, 2025)
This study explains the role of Plan International in reducing child marriage in Sukabumi. Child marriage is a form of violation of children's rights and has a wide range of adverse effects on children, so Plan International contributes to reducing the number of these harmful practices. This is important considering that in Indonesia, the problem of child marriage occurs widely in many regions. One of the regions with a high rate of child marriage is Sukabumi Regency. The author uses the concept of the role of non-governmental organizations by David Lewis and Nazneen Kanji in service delivery, catalyst, and partnership. In this study, responding to this problem, Plan International as INGO played a role through the Yes I Do program in Sukabumi together with various local and international partners to form KPAD, FAD, youth posyandu, equivalent modules and business classes. This research has a time span in 2016-2020, because it is in accordance with the formation and implementation of the program in Sukabumi Regency. This research uses a qualitative method with a descriptive type and data collection is carried out through interviews and literature studies. The researcher found that based on the concept, Plan International through programs and cooperation between actors can reduce child marriage in Sukabumi Regency.